OU Malaysia newsletter, Issue 5, 2003 - Open University Malaysia, (Open University Malaysia (OUM), 2003)
Articles include : MoU between OUM and University La Rochelle; EU-ASIA 2003 E-Learning Conference; Career Certificate in Retail Operations (CCRO) graduation ceremony, etc.